O poder está no prato : breve análise da governança global dos alimentos, seus atores e contradições - Elis Virginia da Silva Santana (2023)
In this dissertation we seek to describe how global governance is organized around the food agenda. Therefore, we aim to investigate and describe how the current global food governance is structured and what the implications of this arrangement are. Accordingly, we discuss aspects of the international political economy and the approach to food regimes, in order to answer the following questions: In which context did the current governance develop? Who are the main parties involved and their interests? How does it address the main contemporary problems related to security and the food system? Our hypothesis is that current global food governance is structured on neoliberal principles, in which private players exert power and influence while their actions contribute to deepening regional inequalities and worsening the food and environmental crisis. In this arrangement transnational agrifood corporations, social movements, international organizations and nations make up the framework of a fragmented governance with a strong dominance of the private paradigm, guided by companies and international financial organizations. However, we observed that this arrangement has been increasingly questioned, not solely for the persistence of hunger in a wealthy world but also due to evidence that relates the current structure of the food system to climate change and the increase in obesity rates worldwide. Alternatives to this model are emerging, especially from civil society, with the food sovereignty agenda being one of the strongest aspects. They bring a proposal to transform this current system into a dual logic, which opposes localism to globalism, natural to processed and sovereignty to security. To build the structure of this work, characterized by a qualitative-descriptive research as we aim to describe and analyse the global governance of food based on the identification of its stakeholders, we used bibliographical research as a method, based on data such as Google Scholar, Biblioteca Digital de Teses e Dissertações, SciELO, Scopus, Periódicos CAPES,, websites of institutions and companies investigated here, as well as international organizations such as FAO, UN and EMBRAPA.